The French menu : the design and development of a web-based application for chefs, restaurateurs and waitrons on the writing and understanding of menus in French - Kulenkampff, Julia (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2008.